Geographic variation in acid–base balance of the intertidal crustacean Cyclograpsus cinereus (Decapoda, Grapsidae) during air exposure. (10th September 2013) - Lagos, Marcelo; Cáceres, Cristián W.; Lardies, Marco A.
Abstract : In intertidal poikilotherms with wide geographic distribution, physiological variations are ubiquitous, due to phenotypic plasticity and/or individual geographic variation. Using the grapsid crab, Cyclograpsus cinereus as a study model, acclimatization differences in respiratory physiology were evaluated among populations along the Chilean coast, covering a latitudinal gradient of about 2000 km. This species inhabits the supratidal zones and, therefore, is subject to constant immersion and emersion periods, producing physiological acidification due to CO2 retention, mainly in the branchial cavity. Individuals of six populations were collected along the coastline of Chile and were exposed to air for different time periods in the laboratory. The following parameters were measured: pH, Ca 2+, Cl − and haemolymphatic lactate dehydrogenase (LDH) enzyme activity. Populations from lower latitudes were significantly different from those from central and southern Chile, with a higher haemolymphatic pH variation and higher Ca 2+ level, along with lower levels of Cl − and LDH enzyme activity. This indicates that the populations from lower latitudes, which are subject to higher air temperatures during emersion, have a higher homeostatic capacity during emersion periods than those of intermediate and higher latitudes. This response seems to be determined by genetic bases due to adaptation to the local environment.